Academic literacies: looking back in order to look forward - Lea, Mary R. (Critical Studies in Teaching and Learning, 2023)
This paper argues that we need to reclaim the institutional perspective that was inherent in some of the early work in the field of academic literacies. It offers a brief overview of the emergence of the field and examines some key developments, including an examination of areas of tension with regard to the use of the term academic literacies. It also points to the ways in which the field is drawing in valuable and complementary theoretical and methodological frames, latterly with respect to significant developments in the digital landscape in higher education. The author concludes that academic literacies researchers have ongoing work to do with regard to the changing contexts of higher education and the need to push against the relentless redefinition of the university for its commercial and transfer value as opposed to its intellectual or critical value.